Fashion and museums : theory and practice / edited by Marie Riegels Melchior and Birgitta Svensson. - Melchior, Marie Riegels, 1974-; Svensson, Birgitta, 1948- (Dress, body, culture., 2014)
"Why is fashion "in fashion" in museums today? This timely volume brings together expert scholars and curators to examine the reasons behind fashion's popularity in the twenty-first century museum and the impact this has had on wider museum practice.Chapters explore the role of fashion in the museum across a range of international case studies including the Costume Institute at the Metropolitan Museum of Art in New York, The Fashion Museum at Bath, ModeMuseum in Antwerp and many more. Contributions look at topics such as how fashion has made museums accessible to diverse audiences and how curators present broader themes and issues such as gender, class and technology innovatively through exhibiting fashion. Drawing on approaches from dress history, fashion studies, museum studies and curatorship, this engaging book will be key reading for students and scholars across a range of disciplines"--